WAR AND SUSTAINABLE DEVELOPMENT - Dhammapathee, Vaishali Sambodhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Great Depression, spanning 1929 to 1939, remains the most protracted and severe economic crisis experienced by the industrialized Western world. Originating in the United States, its impact reverberated globally, causing precipitous declines in output, widespread unemployment, and acute deflation. Beyond its economic devastation, the Depression's social and cultural ramifications were profound and far-reaching. Scholars have attributed the Depression to various factors, including the altered economic landscape following World War I. This paper will examine these explanations, focusing on the concomitant shifts in global production strategies. Furthermore, the policy responses to the Depression engendered significant transformations in the sectoral composition of global production. While these changes fostered economic recovery, they also contributed to the degradation of a crucial public good: the environment. This paper seeks to analyze this environmental cost and explore the various mitigation strategies employed to address it. Finally, this paper aims to juxtapose these modern approaches with the concept of sustainable development as articulated in Buddhist philosophy. Buddhism offers a distinct perspective on sustainability, emphasizing "human-centered development" and presenting a unique framework for harmonizing economic progress with environmental preservation, a framework particularly relevant in the context of the disruptive impact of war on sustainable development.